Respuestas

2012-06-26T06:48:15+02:00

comensemos :

 

11) solucion:

 

raiz  (tan53*sen37*tan^7(45))

            cos60*cos53*cot37

 

raiz   ((4/3)*(3/5)*(1^7))

          (1/2)*(3/5)*(4/3)

 

raiz    (4/3)*(3/5)*(1)  

        (1/2)*(3/5)*(4/3)

 

raiz    12/15

         12/30

 

raiz   12*30

         15*12

 

raiz   2

 

raiz(2)

 

16) solucion:

 

  A+B = pi/4

 

  A+B = 45

 

aplicamos tangente:

 

tan(A+B) = tan(45)

 

  tanA+tanB   =1

 1-tanA*tanB

 

tanA+tanB = 1- tanA*tanB

 

tanA+tanB + tanA*tanB =1

 

17) solucion:

 

sen(x+y)+sen(x-y)=1/2

 

senx*cosy+seny*cosx+senx*cosy-seny*cosx=1/2

 

2senx*cosy=1/2

 

senx*cosy=1/4

 

nos dicen que :

 

secx.coscy=3

 

  1    *   1    = 3

cosx   seny

 

       1      = 3

seny*cosx

 

1=3seny*cosx

 

seny*cosx =1/3

 

nos pide:

 

sen(x+y)=senxcosy +seny.cosx

 

sen(x+y)= 1  +  1

                 4      3

 

sen(x+y)=  7

                  12

 

un gusto....=D